Involvement of matrix metalloproteinases and their inhibitors in Staphylococcus aureus chronically infected bovine mammary glands during active involution - Beccaria, Camila (2021)
The aim of this study was to characterize the protein expression of matrix metalloproteinase-2 (MMP-2) and ‐− 9 and their inhibitors (TIMP-1 and -2) in mammary tissue of dairy cows with naturally occurring chronic S. aureus intramammary infections (IMI) during active involution. Moreover, the gelatinolytic activity of MMP-2 and -9 in mammary secretions was evaluated. Cows in late lactation that were either uninfected or with chronic naturally acquired S. aureus IMI were included in this study. Protein expression of MMP-2 and -9 in mammary tissues was significantly higher in S. aureus-infected than uninfected quarters at day 14 and 21 of involution. Protein expression of TIMP-1 and -2 was significantly higher in S. aureus-infected than uninfected quarters at day 7, 14 and 21 of involution. The MMP-2/TIMP-1, MMP-2/TIMP-2, MMP-9/TIMP-1 and MMP-9/TIMP-2 ratios were significantly higher in S. aureus-infected compared with uninfected quarters at day 14 of involution. The MMP-2 activity was significantly higher in mammary secretions from S. aureus-infected compared with uninfected quarters at day 1, 2, 7 and 14 of involution. The MMP-9 activity was significantly higher in mammary secretions from infected quarters compared with uninfected quarters at day 7, 14 and 21 of involution. The increased expression of MMP-2 and -9 in mammary tissue as well as the high levels of activity observed in mammary secretion from infected quarters compared with uninfected quarters during active involution, strongly suggests that these gelatinases could contribute to degradation of mammary tissue components during chronic S. aureus IMI. The MMPs/TIMPs imbalance could lead to greater proteolysis and potentially more damage to mammary tissue in S. aureus-infected quarters.